A shift of inheritance tradition in Batak migrant communities in Yogyakarta - Widihastuti, Setiati; Nurhayati, Iffah; Kuncorowati, Puji Wulandari; Puspitasari, Chandra Dewi (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
This article examines the shift in customary inheritance in the Batak community that migrated to Yogyakarta. Traditionally, among the Batak people, the patrilineal system is a cultural heritage still preserved today. The enactment of the patrilineal system is one of the causes of the unequal position of Batak women's inheritance rights because only men have the right to become heirs. Interaction with people of different ethnicities, customs, and customs in overseas places not only expands the horizons of Batak nomads but also allows them to change their point of view so that leaving the roots of Batak customs will be inevitable. Until now, some Batak nomads still make boys as heirs, but it is undeniable that there is a mixture of heterogeneous communities in overseas areas that can give rise to a shift in the views of Batak nomads so that they become more open, such as accepting women as heirs with different parts. Equalizing the position between men and women through the division of inheritance indicates a shift in Batak inheritance customs that apply in the environment of the migrants. The emergence of the balance of position between men and women in the implementation of inheritance increasingly shows that the non-maintenance of customary rules that do not give inheritance rights to women is not solely preserving the identity of the Batak Toba people overseas. However, it should be suspected as one of the dynamics that emerged in the settlement of heritage by Toba Batak nomads.